The Influence of Green Innovation, Financial Resources, Technology Usage, and Knowledge Sharing on Sustainable Performance of MSMEs in Kebak - Setyaningsih SU; Edi Wibowo (Global Research Collaboration, 2026)
MSMEs contribute significantly to the national economy, but still face challenges in the form of low sustainability literacy, understanding of environmental risks, and governance readiness. This condition demands an increase in sustainable performance through the implementation of sustainable business practices in MSMEs. Problems related to the sustainable performance of MSMEs in Kebak Village, Jumantono District indicate that most MSMEs still face various obstacles in realizing business sustainability so that the sustainable performance achieved is not optimal. This study aims to explore previous findings to analyze the influence of green innovation, financial resources, technology usage, and knowledge sharing on the sustainable performance of MSMEs in Kebak Village, Jumantono District, Karanganyar. The novelty of this study lies in the integration of green innovation, financial resources, technology usage, and knowledge sharing variables in one model to analyze the sustainable performance of rural MSMEs, focusing on MSMEs in Kebak Jumantono Village, Karanganyar, which have never been studied in the context of MSME sustainability. This study used a sample of 170 MSMEs in Kebak Jumantono Village, Karanganyar. Data used primary sources, collected through questionnaire instruments. The data analysis technique used Partial Least Square Analysis. The results of the study (1) Green innovation does not have a significant effect on sustainable performance (2) financial resources have a significant effect on sustainable performance, (3) technology usage has a significant effect on sustainable performance, and (4) knowledge sharing has a significant effect on sustainable performance. The contribution of this study is expected to provide input for MSMEs, especially in Kebak Jumantono Village, in improving business sustainability through green innovation, technology utilization, strengthening financial resources, and increasing knowledge sharing and become a reference for local governments in formulating sustainability-based MSME development policies.